Critical Evaluation of the Shear Lag Factor Provisions for W-Sections - Alhassan, Mohammad A.; Abdalla, Khairedin M.; AL-Shatnawi, Mohammad E. (Frontiers in Built Environment, 2020)
Shear lagging resulting from non-uniformity of stress distribution around the connection, is one of the important design considerations in steel construction since it reduces the load capacity of tension members. In this paper, the rationality of the AISC provisions for calculating the shear lag factor (U) for W and WT-sections was assessed. In the current AISC provisions, there is an enormous difference in the calculated value of U using two allowed for W and WT sections; yet the AISC allows using the largest value for U. Accordingly, this study was conducted to investigate the reasonable value of U in W and WT-sections based on finite element analysis (FEA). Two criteria were used to calculate this lagging for 50 sizes of W sections and 50 sizes of WT sections. For each section size, three models having different connection length were created, which results in a 150 models for W sections and 150 models for WT-sections. For each section type, the influence of the bolt diameter, the connection eccentricity, flange width, depth, flange area, and gross-sectional area were evaluated individually through a parametric study. It was shown that, the calculated values for U based on the two cases allowed by the AISC provisions were comparable for shallow W and WT sections, but differ enormously for larger sections. Accordingly, a new equation was developed for more reasonable calculation of U for any W and WT standard size.